A ideia de “harém” na Assiriologia e nos Estudos Aquemênidas: uma análise comparativa - Treuk Medeiros de Araujo, Matheus (Classica - Revista Brasileira de Estudos Clássicos, 2023)
Since Near Eastern kings could have multiple wives and concubines, many historians unadvisedly project the Islamic notion of “harem” into the Ancient Near East. However, due to anachronisms, the orientalist connotations of the term, and wrong suppositions concerning the homogeneity of the category of “palace women,” this practice was met with severe criticisms. In this article we endeavor to show how very similar theoretical discussions concerning the “harem” were developed in the fields of Assyriology (focusing on the Neo-Assyrian case) and Achaemenid Studies, sometimes with different outcomes. We argue that since the Achaemenid and Neo-Assyrian Empires constituted a continuity in the longue durée, they should be studied comparatively, and that their respective areas of study may benefit from a diachronic view concerning the issue of royal women.